Feasibility of fused imaging for the evaluation of radiofrequency ablative margin for hepatocellular carcinoma. Issue 7 (30th November 2012) - Tomonari, Akiko; Tsuji, Kunihiko; Yamazaki, Hajime; Aoki, Hironori; Kang, Jong‐Hon; Kodama, Yoshihisa; Sakurai, Yasuo; Maguchi, Hiroyuki
<x xml:space="preserve">Abstract</x> Aim To evaluate the feasibility of fusion of conventional imaging modalities to facilitate assessment of ablative margin of radiofrequency ablation (RFA) of hepatocellular carcinoma (HCC). Methods Two hundred and thirty‐nine liver lesions in 109 patients underwent percutaneous RFA under ultrasound for HCC from January 2008 to December 2010. Within these patients, 13 lesions in 12 patients who developed local tumor progression in the follow‐up period of at least 8 months were retrospectively reviewed. Imaging obtained before and after RFA was used for creating fused images on a workstation. Ablative margins were assessed using only axial images, and with fused images. Results The ablative margin was assessed as sufficient in all 13 lesions using side‐by‐side axial images; however, all lesions were assessed as insufficient with fused imaging evaluation. The reason for the discrepancy of the assessment results were differences in the respiratory dislocation of the liver in the pre‐ and post‐RFA images in eight lesions (61.5%), and rotational displacement of the liver and the torso in five (38.5%). The site of local tumor recurrence relative to the HCC lesion was craniocaudal in 12 lesions, dorsoventral in seven and lateral in seven. In all lesions, the site of local tumor recurrence was congruent with the area of the thinnest ablative margin. Conclusion Assessment of ablative margin with fused imaging revealed insufficiency of ablation previously evaluated as sufficient with conventional axial imaging. Fused imaging evaluation has proved to be an accurate and useful tool for the assessment of RFA margins.